Screening small cardamom (Elettaria cardamomum Maton) field gene bank accessions for phenotypic characters, yield potential and disease resistance - Sharon, A.; Biju, C. N.; Ankegowda, S. J.; Shivakumar, M.S.; Senthil Kumar, R.; Peeran, M. F. (Journal of Spices and Aromatic Crops, 2020)
Evaluation of 117 field gene bank accessions of small cardamom for phenotypic characters along with yield potential and disease resistance (rhizome rot and leaf blight) at ICAR-Indian Institute of Spices Research Regional Station, Appangala revealed significant variation with respect to phenotypic characters. The highest plant height (350 cm) and number of bearing tillers (36.4) were recorded in the accessions, field gene bank (FGB) 65 and FGB 16, respectively. The highest fresh weight of capsules (399.61 g) and maximum number of capsules (244.20) plant-1 were recorded in the accession, FGB 13. Further, based on screening for disease resistance, 35 and 15 accessions of cardamom were identified as resistant to leaf blight and highly resistant to rhizome rot, respectively. Based on the multivariate cluster analysis, 117 FGB accessions were classified into 5 clusters viz., clusters 1 and 2 encompassing equal number of accessions (44), cluster 3 with one accession (FGB 10), clusters 4 and 5 with 8 and 20 accessions, respectively.